Cartografias da formação territorial do Sul e Sudeste do Pará - Hugo Rogério Hage Serra; Thiago Alan Guedes Sabino (Confins)
This work has as main objective to propose a cartography of the South and Southeast region of Pará based on the territorial formation of this region, in which the main historical events of economic nature that alter the territory are considered. In order to develop this work methodologically, this article has a method reading in which the history of the South and Southeast of Pará, with its contradictions, is materialized in the landscape, as well as in the socioeconomic dynamics that evidenced the region intended here. Thus, the South and Southeast region of Pará is the starting point, where history develops and, finally, the result of social manifestations of an economic and cultural nature, above all. The results obtained reveal a cartographic set that takes into account the main historical-economic events in the South and Southeast region of Pará that can be unfolded in different perspectives from different historical matrices.